The Annales Barcinonenses (ca. 1311) in Codex Paris, Bibliothèque Nationale de France, lat. 4671A: Edition and Study (SP) (Edad Media. Revista de Historia, 2017)
In a 1952 study, Coll Alentorn posited the existence of two chronicles belonging to the family of the annales Barcinonenses which he respectively called Chronicon Barcinonense I and Chronicon Barcinonense II. According to this Catalonian scholar, these two works would have been composed in Barcelona in or around 1323, during the reign of James II of Aragon. However, a close analysis of early editions of these two works shows that both are in fact one and the same text, originally encoded in the manuscript Paris, Bibliothèque Nationale de France, lat. 4671A, and that the differences between the edited versions are due to different methods used by the editors. This article also provides the first critical edition of this work, which for lack of a better title I call Annales Barcinonenses anni 1311.
Keywords: annals; historiography; Crown of Aragon; Catalonia; Middle Ages